Simulation of Finite-Size Particles in Turbulent Flows Using the Lattice Boltzmann Method (Communications in Computational Physics, 2018)
Particle laden turbulent flows occur in a variety of industrial applications.While the numerical simulation of such flows has seen significant advances in recentyears, it still remains a challenging problem. Many studies investigated the rheology ofdense suspensions in laminar flows as well as the dynamics of point-particles in turbulence.Here we will present results on the development of numerical algorithms, basedon the lattice Boltzmann method, suitable for the study of suspensions of finite-sizeparticles under turbulent flow conditions. The turbulent flow is modeled by the latticeBoltzmann method, and the interaction between particles and carrier fluid is modeledusing the bounce-back rule. Direct contact and lubrication force models for particle-particleinteractions and particle-wall interaction are taken into account to allow fora full four-way coupled interaction. The accuracy and robustness of the method isdiscussed by validating the velocity profile in turbulent pipe flow, the sedimentationvelocity of spheres in duct flow and the resistance functions of approaching particles.Preliminary results from the turbulent pipe flow simulations with particles show thatthe angular and axial velocities of the particles are scattered around values of meanaxial velocity and shear rate obtained from the Eulerian velocity field.
Keywords: Lattice Boltzmann method; moving bounce-back; turbulent pipe flow; particles in turbulence; finite-size particles; stresslet.